A portrait of adopted programming languages of Portuguese Higher Education Institutions - Sobral, Sónia Rolland (2021)
The increasing difficulty in meeting the needs of the software industry and the benchmarks defined by IEEE and ACM in the adoption of programming languages in Computer Engineering courses offered by higher education institutions in Portugal presents an added difficulty. This difficulty often depends on the profiles that each institution has or intends to characterize the course offered. The objective of this article is to portray the way in which Portugal and Portuguese higher education institutions have organized themselves to respond to the needs of professionals with competences in Computer Engineering, namely in terms of offering courses and places for students, but also in terms of programming language option chosen as initial, as well as the sequence of initial languages.